PERIODIC REGIMES IN THE SOURCE-ENHANCED CONDENSING AERODISPERSE SYSTEM - Zagaynov V.A.; Lushnikov A.A.; Bakhtyreva M.S.; Lutsenko A.O.; Khodzher T.V. (My University, 2007)
At present, the role of atmospheric aerosols in the formation of climatic and weather conditions is commonly accepted. Therefore, the investigation of the processes of aerosol formation in atmospheric conditions is a pressing issue. It is known that the formation of secondary atmospheric particles is caused by intraatmospheric chemical and photochemical cycles, which produce low-volatile vapors of sulfuric acid and high-molecular organics with their subsequent nucleation, condensation growth, and coagulation. Many details of the stage of atmospheric particle growth up to the size of the cloud condensation nucleus are currently unknown. For example, it has been considered up to the present time that the processes of particle growth cannot lead to oscillating regimes in evolving aerodisperse systems. In our paper, we demonstrate that sinks of particles of sufficiently large size in the presence of the source of new particles can lead to decaying oscillation regimes.